Efficacy of group motivational interviewing plus brief cognitive behavior therapy (GMI-BCBT) for replapse within amphetamine users with co-occuring psychological problems at Southern Psychiatric Hospital in Thailand - K.Sinsak Suvanchot (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010